Electrochemical and Spectrophotometric Methods to Assay of Risperidone an Antipsychotic Drug in Pharmaceutical and Biological Samples - Cakirer, Orhan; Hudai Tasdemir, Ibrahim (Asian Journal of Chemistry, 2010)
The electrochemical behaviour of risperidone and its quantitative determination was investigated using voltammetric and spectrophotometric methods. The diffusion coefficient and number of transferred electrons were calculated by using voltammetric methods. Cyclic voltammetricstudies showed that risperidone shows a characteristic adsorption/desorption behaviour on the hanging mercury drop electrode. Therefore, new, rapid, selective and simple electrochemical methods including differential pulse voltammetry, square-wave voltammetry and simple spectrophotometric methods for the direct determination of risperidone in pharmaceutical dosage forms without time-consuming steps prior to drug assay were developed. In these methods limit of detection (LOD) values were found to be range between 1.3 × 10-8 and 6.4 × 10-8 mol L-1. Proposed methods were applied to determine the content of risperidone in commercial pharmaceutical preparations and biological samples. The methods were found to be highly accurate and precise, having a relative standard deviation of less than 4 %.